Analysis of intra-fractional surface motion during adaptive radiation therapy and relation of internal vs. external position for prostate cancer - Macedo-Jiménez, Fernanda; Kalisch, Iris; Simeonova-Chergou, Anna; Boda-Heggemann, Judit; Fleckenstein, Jens; Dreher, Constantin; Giordano, Frank Anton; Stieler, Florian (Radiation oncology, 2025)
Adaptive radiation therapy (ART) allows real-time treatment plan adjustment based on daily anatomical changes but involves a time-consuming workflow. Surface-guided radiation therapy (SGRT) provides precise patient positioning and intra-fractional motion management. This study retrospectively analyses intra-fractional patient motion using SGRT during long-duration radiotherapy (RT) like ART for prostate cancer and further assesses the relation for internal target position measured by cone-beam CT (CBCT) and surface position measured by SGRT. Thirty ultra-hypo-fractionated prostate cancer patients (137 fractions) treated with ART on Ethos (version 1.0, Varian Medical Systems, Siemens Healthineers, Palo Alto, CA, USA) using a ring-mounted SGRT system (AlignRT inBore, Vision RT Ltd., UK) were retrospectively analyzed. The mean and standard deviation values of surface positions across three translational axes of up to 60 min of treatment were analyzed. Further, the translational shifts from the second daily CBCT before irradiation and surface position data were compared to evaluate the agreement between internal and surface position. Correlations between CBCT shifts and SGRT data were assessed with the Wilcoxon paired samples test. The maximum mean (± SD) surface motion was − 2.21 ± 1.27 mm (vertical, at 45 min), 0.22 ± 1.55 mm (longitudinal, at 35 min), and 0.16 ± 0.77 mm (lateral, at 20 min). After the second CBCT shift, the mean (± SD) surface position deviations were − 0.63 ± 1.43 mm (vertical), -0.24 ± 1.63 mm (longitudinal), and 0.05 ± 0.87 mm (lateral) with ranges of 8.30 mm, 10.02 mm, and 6.08 mm on the vertical, longitudinal, and lateral axes, respectively. Significant differences (p < 0.05) were found between CBCT and SGRT on the vertical and longitudinal axes. SGRT revealed a consistent vertical shift over the whole course of long-duration RT and not only for the first minutes of the treatment. Further, SGRT exclusively is not an adequate inter-fractional positioning tool for prostate cancer patients, however additional SGRT-based intra-fractional monitoring can add a value for long duration RT.
Gesehen am 12.06.2025